CAPITALIZING ON THE DIALECTICAL ECONOMY OF HEGEMONY. - Kaplan, Michael (Cultural Studies, 2012)
This essay offers a symptomatic reading of Laclau's On Populist Reason, arguing that his discursive theory of politics remains needlessly trapped within a restricted, recuperative economy of the signifier. As a result, Laclau is characteristically unable either to perform or to recognize precisely the sorts of rhetorical gestures that his theory specifies as paradigmatic of radical politics. The problem emerges with particular urgency and force in Laclau's encounter with the term ‘capitalism’, which in the context of this encounter comes to designate a historically distinctive discursive framework that functions as an unacknowledged precondition for, and blind spot within, the theory of hegemony.